PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION DENGAN ORGANIZATION CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT. Warusalam Textile Pekalongan) - Edy Purwanto (Neraca, 2018)
This research was conducted because employee turnover experienced an increase and to test the effect of Organizational Commitment and Job Satisfaction Against Turnover Intention with Organization Citizenship Behavior as an intervening variable in PT. Watusalam Textile Pekalongan. The study sample consisted of 80 respondents. Sampling is done using the simple random sampling method. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that Organizational Commitment and Job Satisfaction have a positive effect on Organization Citizenship Behavior (OCB). Job satisfaction has a negative effect on turnover intention. Organizational commitment and organization Citizenship behavior does not affect turnover intention and Organization citizenship behavior cannot mediate the influence of organizational commitment and job satisfaction on turnover intention.